The German Lyric of the Baroque in English Translation - Schoolfield, George C. (UNC Studies in the Germanic Languages and Literatures, 1961)
Here are verse translations, with original texts on facing pages, of representative lyrics by ninety-nine poets of the German Baroque. At its original publication, this volume by Schoolfield presented many of the poets to an English-speaking audience for the first time. An extensive introduction discusses the Baroque culture of the German-language realm and brief biographies of the poets conclude the volume.